(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Inthe present study, the examiners proposed to think about the job satisfactionand work motivation of secondary school teachers concerning some demographicvariables. Job satisfaction and work motivation were dealt with as indigentvariables. The autonomous variables embodied gender, sort of schools, showingknowledge and educational qualifications. For the reason for examination,illustrative study strategy was utilized. The sample embodied 400 secondaryschool teachers working in schools found in Rohtak Division associated to HBSEwhat’s more was chosen by Multi-Stage Random Sampling method. Particular DataSheet ready by the agents, Job Satisfaction Scale (JSS) by Dixit (1993) andEmployees Motivation Plan (EMS) by Srivastava (1988) were utilized for theaccumulation of data. The got data was examined utilizing means, S.d’s andt-test. The discoveries of the study uncovered:i) No significant contrast wasfound in the job satisfaction and work motivation of male and femaleteachers ii) There were significantcontrasts around teachers working in government and private schools; moreencountered and less encountered teachers regarding job satisfaction and workmotivation iii) Significant contrast was accounted for in the work motivationof teachers having graduate and post-graduate qualifications.